The Paradigm of Plural Islamic Theology in Indonesia - Sirajuddin M; Moh Dahlan (Universitas Islam Negeri Mataram, 2015)
Indonesia's plural society requires the formulation and relationships of life that are not taken for granted, but must be inclusive, progressive and pluralistic. If there is no scientific paradigm with its plural character, then there will be attitude that tends to be repressive or al-taṭarruf (extreme). The repressive act or the imposition of theological understanding will lead to destruction or conflict. Therefore, this study is formulated as: How paradigm of Islamic theology study can be built in accordance with the interests of its era? How to build a pattern of ideal relationship between the religions in a plural country like Indonesia? Results of this study is that the approach of Islamic theology study will be able to encourage the emergence of paradigm of Islamic study and paradigm on pattern of inter-religion relationship to build paradigm of plural Islamic theology, patterns of relationships and sincere inter-religion cooperation, namely de jure pluralism (being religious), not as de facto pluralism (having religious). DOI: http://dx.doi.org/10.20414/ujis.v19i2.346